PENERAPAN CUSTOMER SATISFACTION INDEX (CSI) DAN ANALISIS GAP PADA KUALITAS PELAYANAN TRANS JOGJA - Siti Husna Ainu Syukri (Jurnal Ilmiah Teknik Industri, 2014)
An increasingly rapid development of the transportation in Yogyakarta led to the increased of congestion in the city. It encourages the Government to provide adequate, safe and convenient public transport for people. One of the local transportation mode is called Trans Jogja. The existence of Trans Jogja then make tight competition of the transportation business in Yogyakarta. Increasing of the intensity of competition and the number of competitors requires the company to provide more satisfactory service than competitors. In order to improve the services, it is necessary to measure the customer satisfaction. This study was measured overall customer satisfaction using the Customer Satisfaction Index (CSI). It is based on five dimensions of service quality i.e. tangibles (physical evidence), reliability, responsiveness, assurance and empathy. Finding shown 68.7542% of the Customer Satisfaction Index (CSI). It means that the Customer Satisfaction of Trans Jogja is still low in overall. This is also proved by the negative value of the gap between expectations and perceptions of customers. Therefore, improvement of the quality of service required in accordance with the priorities that have been generated by this study in order to improve customer satisfaction.